Semantik dan Makna Konotasi dalam Slanga Pelacur - Mary Fatimah, Subet; Muhammad Zaid, Daud (2017)
Negative perspectives towards prostitutes globally disable the study on prostitution goes nowhere further for example when it comes to the usage of prostitution slangs. This is because the nature of prostitution itself is a taboo and an immoral doing. Every single words uttered by prostitutes depict connotative meanings and thus need in depth understanding to reveal those hidden meanings. Hence this research is mainly to analyze the meanings of the slangs in the prostitutions’ language domain. Analyses were done via semantic approach. Findings showed clearer and understandable meanings of the slangs but even though the explicit meanings are known, these slangs are found to be hidden because slangs in the prostitution domain of language are believed to be obscene and vulgar and thus considered improper to be used at public places. In this study, details of prostitutes’ utterances are put forward then just merely making general perspectives